الترادف في اللغة العربية - Masnal Zajuli (Ta'dib, 2011)
Arabic has unique characteristics which are found in other languages. This makes Arabic a flexible language and has high of elasticity. As a result, in fulfilling and maintaining its function as a means for communication, a medium of delivering Islamic information, a tool for recording of knowledge, Arabic has been able to carry out them very well. However, due to its nature, discussing about Arabic cannot be separated from sounds and meanings since language is basically sounds which produced by the speaker to reveal his thoughts and feelings to achieve particular purposes. Sounds (lafaz) are limited while meanings develop in line with the development in science and technology. As a result, the more findings have been made, the more meanings are required to reveal the findings. In this context, the phenomena of single sound implies several meanings or one meaning required more sounds in Arabic are known as isytirak al-lafzi wa al-maknahu wa al-tuudad. Further and deeper studies need to carry out to avoid the possible mistakes in expressing meanings of Arabic words, especially those of the Holy Quran.Kata kunci:  ترادف ,  لغة